2009
DOI: 10.1590/s1516-35982009001000028
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo, consumo e digestibilidade de nutrientes, produção e composição do leite de vacas alimentadas com silagem de milho ou cana-de-açúcar com caroço de algodão

Abstract: RESUMO -Doze vacas foram distribuídas em três quadrados latinos 4 × 4 com o objetivo de avaliar o consumo e a digestibilidade aparente dos nutrientes, a produção e a composição do leite e o comportamento ingestivo. Os tratamentos consistiram de silagem de milho ou cana-de-açúcar contendo 0, 7 ou 14% de caroço de algodão. Na relação volumoso:concentrado estabelecida, 60:40, o tratamento silagem de milho foi superior na maioria dos parâmetros avaliados, como consumo de MS (20,8 kg/dia), produção de leite e leite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
5
0
7
Order By: Relevance
“…The lower Table 2 -Milk production, estimated dry matter intake and stocking rate in Mombasa grass pasture supplemented in the autumn-winter period milk production obtained with this source of forage corroborates the assertion of other authors (Magalhães et al, 2004;Souza et al, 2009), that dairy cows fed with sugarcane produce less than when fed with corn silage. Similar trend was observed with Mantiqueira cows producing between 15 and 30% less when supplemented with black oat and between 5 and 23% less when supplemented with sorghum silage.…”
Section: Resultssupporting
confidence: 84%
“…The lower Table 2 -Milk production, estimated dry matter intake and stocking rate in Mombasa grass pasture supplemented in the autumn-winter period milk production obtained with this source of forage corroborates the assertion of other authors (Magalhães et al, 2004;Souza et al, 2009), that dairy cows fed with sugarcane produce less than when fed with corn silage. Similar trend was observed with Mantiqueira cows producing between 15 and 30% less when supplemented with black oat and between 5 and 23% less when supplemented with sorghum silage.…”
Section: Resultssupporting
confidence: 84%
“…A manutenção de níveis elevados de amônia é, em parte, explicada pelos maiores consumos de proteína verdadeira e pela menor taxa de degradação do caroço de algodão. Os valores médios de consumo de proteína bruta foram de 3,26; 2,48; 2,67 e 2,45 kg/dia (Sousa et al, 2009) para as dietas à base de silagem de milho e cana-de-açúcar com 0, 7 e 14% de caroço de algodão, respectivamente.…”
Section: Resultsunclassified
“…A excreção de alantoína no leite em relação à excreção total de derivados de purina foi de 4,57% e está de acordo com os valores descritos por Valadares et al (1999), de 4,2 a 5,7%; Oliveira et al (2001), de 4,5%; e Souza et al (2006), de 5,7% (Tabela 4). A maior produção de leite nos animais alimentados com silagem de milho e cana-de-açúcar com caroço de algodão (Sousa et al, 2009) explica, em parte, a maior excreção de alantoína no leite, pois, segundo Gonda & Lindenberg (1997), a produção de leite influencia a concentração e a quantidade de alantoína excretada no leite. O valor médio encontrado de N-microbiano, de 198,87 g/dia (Tabela 4), foi semelhante aos obtidos por Mendonça et al (2004) e Oliveira et al (2001), de 193,2 e 193,4, em vacas de produções médias de 18,9 e 22,0 kg leite/dia, respectivamente.…”
Section: Resultsunclassified
“…In this study, although there was no difference for feeding among diets, lower absolute values were observed for feeding time with the HCS diet, and because it presented one of the highest IDM (Table 3), the higher FE expressed in gDM/h is explained. Sousa et al (2009), comparing diets based on corn silage and sugarcane for dairy cows, observed higher DM and NDF in the diet with corn silage compared with sugarcane, but similar times for feeding and rumination, thus allowing higher FE and RE for both DM and for NDF in diets with corn silage. A similar phenomenon occurred in this study for diets based on EGH, CS and HCS compared with diets with sugarcane bagasse.…”
Section: Discussionmentioning
confidence: 90%